Al-Qolaq ‘Inda Mahaarah al-Qiraa’ah lada Thalabah al-Ma’had al-Ulya bi al-Madrasah al-Tsaanawiyyah al-Islaamiyyah al-Hukuumiyyah Batu min Mandzuur Nadzariyyah Sigmund Freud - Mardhiyah, Salwa Qozziyatul; Fitriani, Laily (UIN Maulana Malik Ibrahim Malang, 2023)
Reading skills are one of the important skills that must be possessed by an individual to be skilled in the language. Because language skills have implications for an individual's ability to compete in the international arena in the aspects of scientific communication, economic transactions, and global negotiations. However, in realizing reading skills in an individual, anxiety is found as a problem that has the potential to hinder and complicate it. This paper aims to: 1) Describe the Arabic reading skills of students in Ma'had Al Ulya; 2) Describe the anxiety experienced by students in Ma'had Al Ulya about Arabic reading skills based on Sigmund Freud's perspective. The method used is a descriptive qualitative research method with a case study design. Sources of data in this study were students in Ma'had Al Ulya who experienced anxiety in Arabic reading skills. The researcher as a research instrument uses data collection techniques through observation, interviews, and documentation as well as Miles and Huberman's descriptive analysis techniques. The results showed that: 1) The reading skills of students in Ma'had Al Ulya are the initial reading skills, where an individual can be literate in Arabic reading but has not yet reached the ability to understand the content of the reading (discourse literacy); 2) Anxiety was found in the initial reading skills by students in Ma'had Al Ulya which included reality anxiety, neurotic anxiety and moral anxiety towards Arabic reading. This anxiety is classified by Sigmund Freud as a condition of one's feelings related to concern, anxiety, uncertainty, or fear of facing reality.